Mechanism of electro-acupuncture in alleviating intestinal injury in septic mice via polyamine-related M2-macrophage polarization - Xu, Xinyi; Huang, Xianglong; Xiao, Lu; Wang, Jiabao; Yang, Xiaokun; Wu, Yifan (Frontiers in Immunology, 2024)
Objective The objective of this study was to investigate the impact of electro-acupuncture (EA) on sepsis-related intestinal injury and its relationship with macrophage polarization. Methods A sepsis model was established using cecal ligation and puncture (CLP) to assess the effectiveness of EA. The extent of pathological injury was evaluated using Chiu’s score, the expression of ZO-1 and Ocludin, and the impact on macrophage polarization was examined through flow cytometry and immunofluorescence staining. The expression of spermidine, one type of polyamine, and ornithine decarboxylase (ODC) was measured using ELISA and PCR. Once the efficacy was determined, a polyamine depletion model was created, and the role of polyamines was reassessed by evaluating efficacy and observing macrophage polarization. Results EA treatment reduced the Chiu’s score and increased the expression of ZO-1 and Ocludin in the intestinal tissue of septic mice. It inhibited the secretion of IL-1β and TNF-α, promoted the polarization of M2-type macrophages, increased the secretion of IL-10, and upregulated the expression of Arg-1, spermidine, and ODC. However, after depleting polyamines, the beneficial effects of EA on alleviating intestinal tissue damage and modulating macrophage polarization disappeared. Conclusion The mechanism underlying the alleviation of intestinal injury associated with CLP-induced sepsis by EA involves with the promotion of M2-type macrophage polarization mediated by spermidine expression.